RACK1 affects the progress of G2/M by regulating Aurora-A. Issue 18 (17th September 2019) - Shen, Suqin; Feng, Huan; Le, Yichen; Ni, Jun; Yu, Long; Wu, Jiaxue; Bai, Meirong
ABSTRACT: Aurora-A is a serine/threonine kinase, which is overexpressed in multiple human cancers and plays a key role in tumorigenesis and tumor development. In this study, we found that the receptor of activated C-kinase1 (RACK1), an important regulator of biological functions, interacted with Aurora-A and co-localized with Aurora-A at centrosomes. Moreover, RACK1 induces the auto-phosphorylation of Aurora-A in vitro and in vivo. Depletion of RACK1 impaired the activation of Aurora-A in late G2 phase, then inhibited the mitotic entry and leaded to multi-polarity, severe chromosome alignment defects, or centrosome amplification. Taken together, these results suggest that RACK1 is a new partner of Aurora-A and play a critical role in the regulation of the Aurora-A activity during mitosis, which may provide a basis for future anticancer studies targeting Aurora-A.